Structural failure test of a 52.5 m wind turbine blade under combined loading. (September 2019) - Zhang, Lei'an; Guo, Yanzhen; Wang, Jinghua; Huang, Xuemei; Wei, Xiuting; Liu, Weisheng
Abstract: Blade is one of the basic and key components in wind turbines. To get closer to the actual loading condition of blade under complex and extreme wind conditions to more accurately analyse the structural failure characteristics of large wind turbine blades. The structural collapse test of a 52.5 m wind turbine blade under combined loading was carried out. The entire process of damage under ultimate load was recorded and analysed in detail. The joint analysis of the failure region after the blade collapse and the failure mode during the test process were performed. The research shows that the geometrical nonlinear buckling of spar cap and shear web, the delamination result from non-uniform stress distribution and further fracture of Aft panel cause catastrophic failure of the blade. The torsional moment cause oblique cracks and oblique bulges, aggravates the expansion of the internal and external composite cracks of blade, affects the final failure mode after blade collapses (critical failure mode), and make the spar cap at suction side to clockwise twist from blade tip to root. The research results lay a theoretical foundation for subsequent model establishment and simulation analysis of large wind turbine blades under combined loading. Highlights: Composite loads of bending and torsion are closer to actual extreme wind conditions. The joint analysis of failure modes during test and after collapses is direct and convincing. Torsional moment causes oblique crack and oblique bulge, which aggravates composite cracks and effects critical failure mode. The coupling mechanism of buckling, delamination and debonding is reconstructed.